Research of the impact of the terrorism and other factors on the consumers behavior - Horiachko, Kateryna (Technium Social Sciences Journal, 2020)
The purpose of this study is to identify the main factors influencing consumer’s behavior while travelling to Ukraine. The object of the study was the sample of people who are consumers of touristic services in Ukraine. The main hypothesis of the study was that consumer’s behavior depends on variety of factors in Ukraine, including but not limited to military conflict or terrorism. To improve the knowledge about various factors impact on consumer’s behavior the factor analysis was used, joined by a method of a principal components analysis in SPSS. Using the SPSS the main factors were determined.